Macrofauna Community Structure on Seagrass Meadows of Sampadi Island, Lundu, Sarawak - Shabdin, Mohd Long; Mohamad, Zakirah; Norzamratul, Taufek (2014)
Seagrasses serve as habitats to many marine organisms including macrofauna. The study on macrofauna community structure in seagrass meadows at Sampadi Island, Sarawak was conducted in October 2012. The objectives were to determine the macrofauna community structure and its relation with physico-chemical parameters of the water in Sampadi Island. A transect line was laid down from high to low tide marks on the intertidal area of the island. A 0.25 m -2 quadrat was used to sample the sediment and sieved using the 500 µm sieve. The macrofauna retained on 500 µm sieve were identified in the laboratory using various keys in the literature with the aid of stereo-and compound microscope. Five macrofauna phyla were recorded in the seagrass meadows, namely Mollusca (Cardiidae & Veneridae), Annelida (Dorvillea sp., Eulalia sp., Eteone sp., Cirriformia sp. & Tubificoides sp.), Sipuncula (Sipunculidae), Arthropoda (Alpheus sp., Harpacticus sp. & Colomastix sp.) and Chordata (Branchiostoma sp.). The community structure of macrofauna in seagrass meadows of Sampadi Island was influenced by the dissolved oxygen, sediment grain size, salinity and temperature.